Creative practice as mutual recovery in mental health - Crawford, Paul; Lewis, Lydia; Brown, Brian; Manning, Nick (Emerald Group Publishing Limited, 2013)
Abstract Purpose – The purpose of this paper is to examine the value of approaches to mental health based on creative practice in the humanities and arts, and explore these in relation to the potential contribution to mutual recovery. Design/methodology/approach – The paper is a conceptual analysis and literature review. Findings – Recovery can embrace carers and practitioners as well as sufferers from mental health problems. Divisions tend to exist between those with mental health needs, informal carers and health, social care and education personnel. Mutual recovery is therefore a very useful term because it instigates a more fully social understanding of mental health recovery processes, encompassing diverse actors in the field of mental health. Research demonstrates the importance of arts for “recovery orientated mental health services”, how they provide ways of breaking down social barriers, of expressing and understanding experiences and emotions, and of helping to rebuild identities and communities. Similarly, the humanities can advance the recovery of health and well-being. Originality/value – The notion of mutual recovery through creative practice is more than just a set of creative activities which are believed to have benefit. The idea is also a heuristic that can be useful to professionals and family members, as well as individuals with mental health problems themselves. Mutual recovery is perhaps best seen as a relational construct, offering new opportunities to build egalitarian, appreciative and substantively connected communities – resilient communities of mutual hope, compassion and solidarity. Keywords Mental health, Recovery, Mutuality, Health humanities, Arts, Humanities, Mental health services